Factoriser les expression suivantes + souligner leurs facteurs commun de chaque expression : (détailler les calculs )

1) 5x + 2x + 10x

2) 27x² - 27x + 27

3)9x ( x-3 ) + 9x (10+2x)

4) ( 2x + 1 ) ( 8 + x ) - (3x - 1 ) (2x + 1 )

1

Réponses

  • Utilisateur Brainly
2014-04-06T16:20:57+02:00
1)   5x + 2x + 10x
  =x(5+2+10)
  =17x

2)  27x² - 27x  + 27
  =27(x²-x+1)

3)9x ( x-3 ) + 9x (10+2x)
=(9x)(x-3+10+2x)
=(9x)(3x+7)

4)  ( 2x + 1 ) ( 8 + x ) - (3x - 1 ) (2x + 1 )

=(2x+1)(8+x-3x+1)
=(2x+1)(-2x+7)